Foundation studies with physical modeling - Osamu Kusakabe (Soils and Foundations)
This contribution is part of a series of invited papers on “A Review of the Author’s Own Seminal Contributions”. The paper describes the author’s 45 years of research experiences with a focus on foundation studies with physical modeling. Following some general statements on physical modeling, the facilities that the author utilized are described; and subsequently, the selected foundation problems that he tackled are explained mainly from physical modeling viewpoints. The selected problems cover shallow/ deep foundation stability problems and a few geoenvironmental issues, such as ground vibrations and piling at post-closure waste disposal sites. The outcomes of his research offered engineering solutions that society needs. The paper emphasizes the usefulness of the methodology of combining the theory of plasticity and physical modeling.